2022
DOI: 10.1155/2022/1201977
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Liraglutide 3.0 mg in Patients with Overweight and Obese with or without Diabetes: A Systematic Review and Meta-Analysis

Abstract: Background. Liraglutide in a 3.0 mg subcutaneous dose daily is approved for weight reduction. Objectives. Objectives are to evaluate the efficacy and safety of liraglutide 3.0 mg in patients with overweight and obesity irrespective of diabetic status. Methods. We conducted an electronic database search in PubMed, Embase, and https://ClinicalTrial.gov to identify all randomized control trials (RCTs) that evaluated the efficacy and safety of liraglutide 3.0 mg dose compared to placebo in overweight (≥27 kg/m2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…More importantly, once-weekly semaglutide increased the weight loss of at least 10% (53% more) and 15% (33% more) compared with placebo. The significant numbers were notably higher than those observed in previous studies involving other anti-obesity medications within a similar patient population [35,36].…”
Section: Accepted Manuscriptcontrasting
confidence: 71%
“…More importantly, once-weekly semaglutide increased the weight loss of at least 10% (53% more) and 15% (33% more) compared with placebo. The significant numbers were notably higher than those observed in previous studies involving other anti-obesity medications within a similar patient population [35,36].…”
Section: Accepted Manuscriptcontrasting
confidence: 71%
“…Liraglutide also led to a signi cant reduction in body weight (MD: -5.04 kg), BMI (MD: -1.95 kg/m 2 ), and waist circumference (MD: -3.64 cm), with a higher percentage of participants achieving 5% and 10% weight loss [13].…”
Section: Discussionmentioning
confidence: 94%
“…Chronic cardiovascular and cerebrovascular conditions are thought to be caused by the synergistic effect of diabetes or prediabetes with hypertension on forming calcified arterial plaques, especially in the coronary and cerebral arteries [12,13]. This metabolismdisease relationship is proven by reports that mortality risks decrease observably upon loss of fat from the central trunk [14][15][16][17]. Furthermore, studies of glucose-controlling drugs that result in smaller waistline circumference and large population studies have observed decreased odds ratios of diabetic and cardiovascular risks after moderate weight loss [14,18].…”
Section: Obesity Diabetes the Heart And The Brain: A Troublesome Tetradmentioning
confidence: 99%